Aplikasi Augmented Reality Untuk Pengenalan Mata Uang ASEAN Berbasis Android - Tresnawati, Dewi; Pardiansyah, Irgi (Jurnal Algoritma, 2025)
An Augmented Reality (AR) based ASEAN currency recognition application was developed to provide an interactive experience in recognizing the currencies of ASEAN countries. Different from previous research that only displays static information, this application integrates AR technology with additional features such as 3D visualization of currencies, automatic detection of real-time exchange rates through global APIs, as well as an interactive interface designed to enhance user understanding. By utilizing the Vuforia Engine, the app can accurately recognize banknotes from Indonesia, Malaysia, Philippines, Singapore, and Thailand and display details of the denomination, dimensions, and security elements of each currency. Development was conducted using the Multimedia Development Life Cycle (MDLC) method which includes the stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Testing using Black Box and Beta Testing methods showed that this application runs according to the designed specifications and received positive responses from users. With its innovative features, this application has the potential to improve financial literacy in the ASEAN region through a more interactive and accessible approach.